2017
DOI: 10.1016/j.artd.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Academic productivity among fellowship associated adult total joint reconstruction surgeons

Abstract: BackgroundThe Hirsch index (h-index) is a measure that evaluates both research volume and quality—taking into consideration both publications and citations of a single author. No prior work has evaluated academic productivity and contributions to the literature of adult total joint replacement surgeons. This study uses h-index to benchmark the academic impact and identify characteristics associated with productivity of faculty members at joint replacement fellowships.MethodsAdult reconstruction fellowship prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…[8][9][10][11][12][13] For example, Yang et al 14 demonstrated a strong relationship in the field of urology between increased publication output during residency and the pursuit of fellowship training or a future career in academic medicine. These same relationships have been found among residency graduates in multiple specialties such as emergency medicine, 15 orthopedic surgery, 16,17 ophthalmology, 18 pediatrics, 19 and plastic surgery, 20,21 among others. Although several reports show promising results, investigations of publication trends among internal medicine and neurosurgery residency graduates have yielded conflicting findings.…”
Section: Introductionsupporting
confidence: 62%
“…[8][9][10][11][12][13] For example, Yang et al 14 demonstrated a strong relationship in the field of urology between increased publication output during residency and the pursuit of fellowship training or a future career in academic medicine. These same relationships have been found among residency graduates in multiple specialties such as emergency medicine, 15 orthopedic surgery, 16,17 ophthalmology, 18 pediatrics, 19 and plastic surgery, 20,21 among others. Although several reports show promising results, investigations of publication trends among internal medicine and neurosurgery residency graduates have yielded conflicting findings.…”
Section: Introductionsupporting
confidence: 62%
“…In another research, Schoenfeld et al (2015) found that academic affiliation and number of fellows in a program was significantly associated with total number of publications. Similarly, Khan et al (2017) found that number of fellows, faculty academic title, years in practice, and formal fellowship training had a significant positive correlation with both h-index and number of publications of medical university faculty. Thus, we proposed our first hypothesis: H1: Higher institution of bigger size has higher research productivity than smaller ones.…”
Section: Sizementioning
confidence: 81%
“…Scholarly productivity and scientific impact are key to measuring the accomplishment, value, and contribution of individual academicians within academic emergency medicine departments . The use of bibliometric measures to quantify scholarly performance has been growing across academic medicine . The number of peer‐reviewed papers published is a common measure of productivity used to evaluate performance for hiring and promotion purposes despite significant limitations with this metric .…”
mentioning
confidence: 99%